"Enculturalling" Multilingualism: Family language ecology and its impact on multilingualism. Issue 2 (3rd April 2021) - Cavallaro, Francesco; Xin Elsie, Tay Ya; Wong, Francis; Chin Ng, Bee
ABSTRACT: Though the two languages most frequently used in the homes of Chinese Singaporeans are English and Mandarin Chinese, there is not much information on how the home language can influence language use and attitudes toward these two languages. This study investigates the family language ecology in bilingual homes and aims to compare attitudes toward Mandarin Chinese between Chinese Singaporean young adults from English-speaking homes (ESH) and those from Chinese-speaking homes (CSH). A total of 118 participants took part in a questionnaire designed to elicit language use and attitudes toward Mandarin. Results reveal that participants from Chinese-speaking homes do show greater use and proficiency in Mandarin, as well as possess more positive attitudes and motivation toward Mandarin as compared to participants from English-speaking homes. Both group report using more English with their siblings than their parents. However, the CSH group reports using more Mandarin than English with their siblings and more so with their younger siblings. This study emphasizes the process of "enculturation" to be an essential feature of language maintenance and as the home is the main site for enculturation to take place this study has implications for language maintenance for minority languages.